Gamification In Occupational Safety Training: A Systematic Literature Review - Condori Colan, Cesar Alonso Nazael (2023)
Gamification is a new methodology that is used mainly in education and marketing, however, in recent years it has become more relevant in the training of personnel at a professional level. The objective of this literature review was to make a synthesis and analyze the cases of gamification implementation in training both at a professional level and at a level of student practices. The following review was based on the PRISMA model, studies were delimited by inclusion criteria, and finally, after discarding articles, 39 studies remained for analysis. The results of this investigation determined that gamification is an innovative way of training that promotes growth, the development of competences and teamwork. Likewise, it was evidenced that gamification was implemented more in the field of medicine and there is a gap of knowledge of the implementation of gamification in other professional areas.